Influence of Adsorption Kinetics upon the Electrochemically Reversible Hydrogen Oxidation Reaction - Lin, C; Jiao, X; Tschulik, K; Batchelor-Mcauley, C; Compton, R (American Chemical Society, 2015)
The hydrogen oxidation reaction was studied at bright polycrystalline platinum microelectrodes. A smaller steady-state current was observed in experiment as compared to that anticipated for a diffusion limited process. To facilitate physical insight into this system, a simulation model based on the Tafel-Volmer mechanism for the hydrogen oxidation reaction was developed. Under conditions of reversible electron transfer, the adsorption kinetics ka and kd are found to have distinctly different influences upon the voltammetry responses. Correspondence between the simulated and the experimental voltammograms is found, confirming the decrease of the steady-state current is caused by the slow adsorption process. The combined adsorption parameter kaγmax2 on the Tafel-Volmer mechanism was approximately 5.0 × 10-4 m s-1, where γ max (mol m-2) is the maximum surface coverage of adsorption hydrogen atoms.